Consumo de alcohol y sustancias psicoactivas en adolescentes mestizos e indígenas del cantón Saraguro, provincia de Loja. - Cabrera León, Lizbeth Katherine (2016)
The consumption of alcohol and psychoactive substances is a problem that is affecting globally, especially to vulnerable groups such as adolescents. That is why this descriptive, epidemiological and cross-sectional study was conducted, in order to identify and describe the consumption of alcohol and substances Psychoactive by mean of the analysis of the age of onset, the scale of consumption and being able to examine the risk and protection factors of mestizos as well as indigenous adolescents from Saraguro city. The sample was of 450 adolescents aged 12 to 19 years, of whom, 228 were men and 222 women, who were given a survey of 155 questions for data collection. These ones were tabulated by using absolute frequency measures and the percentage as a statistical method to identify and describe the consumption of alcohol and psychoactive substances in these adolescents. In this research work, it was concluded that alcohol is the substance most consumed by adolescents with 62.28% in men and 41.44% in women; followed by marijuana with 17.11% in men and 4.95% in women. This consumption is constituted in its majority by males of indigenous nationality Plant drugs, inhalants, base paste, cocaine, heroin, and ecstasy reflect insignificant percentages.. Among the most important risk factors is easy access to alcoholic beverages, while the main protective factors are the dialogue beetween the family and good relations with it. Key words: Consumption, Psychoactive Sustnces, Alcohol, Adolescents, Risk Factors and Protective Factors.